Fabrication And Characterization Of Uv-Crosslinked Pdms Hydrogel - Thai, Gar Lock (Universiti Sains Malaysia, 2017)
Hydrogel is one of the biomaterial that is suitable for tissue engineering. Hydrogel is defined as polymeric structure that swollen when expose to water. Polydimethylsiloxane is commonly used biomaterials for tissue engineering due to inert and nontoxic properties. However, there is the main drawback of polydimethylsiloxane which it is hydrophobic in nature. To overcome this limitation, polydimethylsiloxane was crosslinked with polyethylene glycol in order to enhance it hydrophilic property. Allyl methacrylate and polydimethylsiloxane 1k was utilized as reactive diluent to form ultraviolet crosslinked hydrogel. Polydimethylsiloxane-SiH and Polydimethylsiloxane-MA that was synthesized had been confirmed with Fourier transform infrared (FTIR) spectroscopy and Nuclear magnetic resonance (NMR). Ultraviolet crosslinked hydrogel had been characterized by swelling test, Scanning Probe Microscopy (SPM), Differential Scanning Calorimetry (DSC), contact angle and Texture Profile Analysis (TPA). From the analysis, it was found that increasing in reactive diluent content had no significant effect on swelling, more stable crystal structure, increased in hardness value and decreased in adhesiveness and resilience and fluctuating effect on contact angle. It also found that with increasing polyethylene glyco content, phase separation happens at a more severe level, swelling percentage had increased, recrystallization peak form, fluctuating effect on hardness value, decreased in adhesiveness and resilience and contact angle decreased.